Normative values for circadian and ultradian cardiovascular rhythms in childhood - Hadtstein, Charlotte; Wühl, Elke; Soergel, Marianne; Witte, Klaus; Schaefer, Franz (Hypertension, 2004)
To assess the prevalence and characteristics of physiological circadian (24-hour) and ultradian (12-, 8-, and 6-hour) rhythms of mean arterial blood pressure (BP) and heart rate (HR), we analyzed 24-hour ambulatory BP profiles from 938 healthy school children aged 5 to 18 years. Cosine harmonics were fitted by Fourier analysis, and an amplitude and acrophase (time of peak) were calculated for each rhythm.
Members of the German Study Group on Pediatric Hypertension are Marianne Soergel, Martin Kirschstein, Thomas Danne, Jutta Gellermann, Reinhard Holl, Friedrich Krull, Hagen Reichert, György S. Reusz, Wolfgang Rascher
Gesehen am 13.01.2021